ANALISIS KEBIJAKAN PENGIKATAN HUBUNGAN, KEPUASAN PELANGGAN DAN LOYALITAS PELANGGAN OPERATOR SELULER XL SURVEI DI MARGO CITY, DEPOK - Budiman Budiana (Universitas Mercu Buana, 2013)
Abstract: Along with the development of time and technology, telecommunications becoming something that is very important. With the numbers of companies/operators that provide telecommunications service, therefore the competition between the telecommunications business company can not be avoid. As for XL, to have a relationship with the customer may give a positive value apart, because the company can maintain existing customers so that consumers are sure on the value for themselves and not easy to switch to other companies products. Therefore relationship bonding is very necessary. This research was conducted to find out how the assessment of the customer relationship bonding the XL and the impact on customer satisfaction and what the impacton customer loyalty. In this research, data collection method was to survey using questioner. Research method used was descriptive method of research.Methods of data analysis using the average score of weight, likert-scale, regression, correlation and analysis. The result of this research shows that customers rate policy relationship bonding XLis good enough. In addition there is the influence of the bonding relationship between customer satisfaction. Research also shows that policy fastening relationship (bonding relationship) that affect customer satisfaction, the impact on customer loyalty. From the results of this research, it can be concludedthat customers are satisfied with the relationship bonding policy made by XL. So that it creates customer loyalty and brand of product or company XL.Keywords: Market competition, customer relationship, retain consumers